ANALISIS EFEKTIFITAS IKLAN MEDIA TELEVISI PADA SEPEDA MOTOR YAMAHA MIO DI KOTA JAMBI - Rahmatullah . (DIGEST MARKETING, 2017)
Te reserearch purpose is 1) to reveal the implementation of television media advertising and 2) to explain theadvertising effectiveness on television for the motorcycle of Yamaha Mio at Jambi City. The data is colected by using seruvey and questionaire. The analysis used EPIC Model to quantify the advertising effectiveness. The result shwos that based on EPIC dimension, theadvertising has effective effect. Hence, firm could design action that connects to this EPIC construct. Keywords. Televison, Advertising effectiveness, and Motorcyle